Für eine neue hermeneutische Theologie - Tétaz, Jean-Marc; Leiner, Martin 1960- (2021)
Article and theses basically describe the program of a New Hermeneutical Theology. The article explains how the New Hermeneutical Theology relates to the classical Hermeneutical Theology of Ernst Fuchs, Gerhard Ebeling and Eberhard Jüngel, and to actual theological programs in Germany, such as Ingolf Dalferth, Christian Danz, and Folkart Wittekind. New Hermeneutical Theology's main systematic proposition is to work on the ground of linguistic and philosophical understandings of language and to consider language as a level where a fruitful dialogue between theology, Humanities and Social Sciences can take place. Paul Ricoeur is a main source of inspiration for the New Hermeneutical Theology. Already since the 1960ies, Ricoeur elaborated a hermeneutic grounded in a theory of language. This led to critical and constructive discussions with Hermeneutical Theologians. The theses show some of the systematical coherences of the New Hermeneutical Theology and its impact on different areas of Dogmatic and Ethics.
Keywords: Jüngel, Eberhard -- 1934-2021